Identification and In-Silico analysis of a cellulose synthase-like gene on eddoe taro - Maretta, Delvi; Helianti, Is; Purwoko, Devit; Santosa, Edi; Sobir (Penerbit Universiti Kebangsaan Malaysia, 2025)
Glucomannan is a non-starch carbohydrate predominantly found in tubers, serving as a significant resource for food and health industries. Despite the widely recognized glucomannan content in taro tubers, there is limited understanding regarding the gene level. Therefore, this research aimed to identify putative Cellulose Synthase-like A (CslA) gene sequences associated with glucomannan biosynthesis in eddoe taro plant. Genome isolation was carried out on six genotypes of eddoe taro, each showing different glucomannan content. A pair of primers designed from the mannan synthase encoding gene sequences obtained from the NCBI. Subsequently, sequences of the PCR product were analyzed for identification and in-silico analysis. The result of in-silico RFLP analysis showed that six genotypes had polymorphic allelic fragments. The DNA sequences showed a high similarity to CslA gene, among representative taro tubers compared to the reference plants. A total of three nucleotide sequences fragments from the S7 and S34 genotypes as well as two from S15, S28, S30, and S36, corresponded to CslA gene of Amorphophallus konjac. Phylogenetic analysis based on nucleotide sequences showed that S7 and S34 had distinctive characteristics, indicating specific and wide adaptation, respectively. Despite the presence of single nucleotide polymorphism, the in-silico transcription-translation showed that the protein constructed had a highly similar consensus motif. These results suggested the identified sequences as a potential CslA-encoding gene that had functioned in the biosynthesis of mannan synthase to produce glucomannan in taro plants.